2013
DOI: 10.1242/jcs.127811
|View full text |Cite
|
Sign up to set email alerts
|

S-adenosylmethionine limitation induces p38 mitogen activated protein kinase and triggers cell cycle arrest in G1

Abstract: The primary methyl group donor S-adenosylmethionine (SAM) is important for a plethora of cellular pathways including methylation of nucleic acids, proteins, and the 59 cap structure of mRNAs, as well as biosynthesis of phospholipids and polyamines. In addition, because it is the cofactor for chromatin methylation, SAM is an important metabolite for the establishment and maintenance of epigenetic marks. Here, we demonstrate that cells halt proliferation when SAM levels become low. Cell cycle arrest occurs prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 53 publications
(71 reference statements)
4
45
0
Order By: Relevance
“…This latter observation, coupled with the findings that the stimulatory effects of SAM are reduced in cells with CBS silencing or in the presence of the CBS inhibitor AOAA are consistent with the hypothesis that a significant portion of the stimulatory proliferative and bioenergetic effects of SAM seen in the current study are, in fact, related to intracellular H 2 S, and its downstream effects. In this context, it is also noteworthy that earlier studies found that intracellular SAM levels are highest during the proliferative phase of various cells [49] while recent studies demonstrated that depletion of endogenous SAM levels leads to a suppression of cell proliferation [50]. These findings are consistent with the hypothesis that SAM, at low/endogenous levels serves as a pro-proliferative, rather than antiproliferative molecule.…”
Section: Discussionsupporting
confidence: 82%
“…This latter observation, coupled with the findings that the stimulatory effects of SAM are reduced in cells with CBS silencing or in the presence of the CBS inhibitor AOAA are consistent with the hypothesis that a significant portion of the stimulatory proliferative and bioenergetic effects of SAM seen in the current study are, in fact, related to intracellular H 2 S, and its downstream effects. In this context, it is also noteworthy that earlier studies found that intracellular SAM levels are highest during the proliferative phase of various cells [49] while recent studies demonstrated that depletion of endogenous SAM levels leads to a suppression of cell proliferation [50]. These findings are consistent with the hypothesis that SAM, at low/endogenous levels serves as a pro-proliferative, rather than antiproliferative molecule.…”
Section: Discussionsupporting
confidence: 82%
“…For instance, iNOS, which may play a role in hypoosmoregulation, localizes to small cells buried deep within gill filaments (Ebbesson et al, 2005). Enhanced expression of the methionine cycle, specifically methionine adenosyltransferase, is also regarded as essential in regulating cell cycle turnover rates (Lin et al, 2014), which complements the results from this study (Fig. 5).…”
Section: Research Articlesupporting
confidence: 84%
“…BHMT, the only known enzyme that uses betaine as substrate, converts homocysteine to methionine [25]. Then, methionine can be converted to S-adenosylmethionine (SAM), the most important methyl donor in the body, by methionine adenosyltransferase (MAT) [26]. SAM is converted to S-adenosylhomocysteine (SAH) after donating its methyl group for different methylation reactions catalyzed by various methyltransferases.…”
mentioning
confidence: 99%